Crystal structure of zebrafish complement 1qA globular domain. (13th September 2016) - Yuan, Hongyu; Chen, Rong; Tariq, Mansoor; Liu, Yanjie; Sun, Yaping; Xia, Chun
Abstract: C1q contains three globular domains (C1qgD) that are the key functional component of the classical complement system. C1qgD can interact with important immune molecules, including IgG and C‐reactive protein (CRP) to form defense systems to protect animals. Here, the first non‐mammalian structure, zebrafish C1qA globular domain ( Dare ‐C1qAgD) was solved. Although the overall architecture of Dare ‐C1qAgD is similar to human C1qA, residues involved in C1qBgD, C1qCgD, and CRP binding are somewhat different while residues involved in IgG binding are not present in zebrafish. The structure gives insight into how human and fish C1qA evolved from an ancestral protein. Abstract : PDB Code(s):5HBA